Growth and Development of Some Genotype of Cassava (Manihot esculenta Crantz.) - Ria Arta Junistia; Emmy Harso Kardhinata; Diana Sofia Hanafiah (Universitas Sumatera Utara, 2018)
The objective of the research was to determine the different of growth and development of some cassava genotype. The research was conducted at Desa Tanjung Selamat, Kecamatan Sunggal, Kabupaten Deli Serdang from July to December 2016. The research was arranged by Randomized Block Design for one variety (Adira-1) and 6 genotype (Valencia, Malang, Malaysia, Lampung, and Putih) each treatment was replicated 4 times.The result showed that Pulut genotype has the highest average plant heigth (277,48 cm) that is significantly different from the others accept Malang genotype, Malang genotype has the highest average diameter (31,26 mm) wich is significantly different from the others. The highest Lobus length character is at Pulut genotype (22,6 cm) and the highest lobus wide is at Malang genotype (7,3 cm). The highest leaf length petiole character is at Putih genotype (31,4 cm), and the highest of leaf lobus character at Adira 1 and Lampung genotype are 5 leaves lobus. There are was different among genotypes (Valencia, Malang, Malaysia, Lampung, and Putih) and variety (Adira-1) on the average weight of (6 month after planted) cassava. Keywords: cassava genotype, development, growth